Detecting SARS-CoV-2 neutralizing immunity: highlighting the potential of split nanoluciferase technology. (13th April 2022) - Jeremiah, Sundararaj Stanleyraj; Miyakawa, Kei; Ryo, Akihide
Abstract: The coronavirus disease 2019 (COVID-19) pandemic has progressed over 2 years since its onset causing significant health concerns all over the world and is currently curtailed by mass vaccination. Immunity acquired against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) can be following either infection or vaccination. However, one can never be sure whether the acquired immunity is adequate to protect the individual from subsequent infection because of three important factors: individual variations in humoral response dynamics, waning of protective antibodies over time, and the emergence of immune escape mutants. Therefore, a test that can accurately differentiate the protected from the vulnerable is the need of the hour. The plaque reduction neutralization assay is the conventional gold standard test for estimating the titers of neutralizing antibodies that confer protection. However, it has got several drawbacks, which hinder the practical application of this test for wide-scale usage. Hence, various tests have been developed to detect protective immunity against SARS-CoV-2 that directly or indirectly assess the presence of neutralizing antibodies to SARS-CoV-2 in a lower biosafety setting. In this review, the pros and cons of the currently available assays are elaborated in detail and special focus is put on the scope of the novel split nanoluciferase technology for detecting SARS-CoV-2 neutralizing antibodies.